O027 The combination of mandibular advancement devices (MAD) and supplemental oxygen dramatically improves OSA severity: preliminary results from the MADOX trial. (7th October 2021) - Edwards, B; Vena, D; Thomson, L; Gikas, A; Radmand, R; Calianese, N; Hess, L; Landry, S; Joosten, S; Hamilton, G; Wellman, A; Sands, S
Abstract: Introduction: Patients with obstructive sleep apnoea (OSA) considered 'non-responders' to mandibular advancement device (MAD) therapy, typically have a high loop gain contributing to their OSA physiology. While MAD does not improve loop gain, other treatments such as supplemental oxygen can have a strong effect on this pathogenic trait. Therefore, we conducted a randomised controlled trial (RCT) to determine whether the administration of supplemental oxygen in combination with a MAD, was associated with greater improvements in OSA severity compared to MAD therapy alone. Methods: Patients recently diagnosed with OSA underwent an initial screening sleep study to confirm the presence of moderate-severe OSA (Apnoea-hypopnoea index [AHI]>20events/hr). Eligible patients were then enrolled in a randomised single-blind cross-over trial involving 4 sleep studies with the following treatments; MAD, oxygen (4L/min), MAD+oxygen and room-air/sham (control). The primary outcome was the reduction in AHI (%baseline). Results: Of the 57 participants screened, 35 met the eligibility criteria (Baseline/Screening AHI = 52±22 events/hr). Compared to the sham night, all treatments significantly reduced the AHI; a 35% [CI: 18–48] was seen with oxygen (p<0.0002), a 53% [CI: 40–64] was seen with MAD (p<0.0001) and a 67% [CI: 56–76] was seen with MAD+oxygen (p<0.0001). Importantly, the combination of MAD+oxygen was associated with a significant reduction in AHI relative to MAD alone (15% [CI:4–24] p=0.01). Discussion: In a population with moderate-severe OSA, preliminary analyses from this trial suggests that the addition of supplemental oxygen in combination with MAD therapy provided greater reductions in OSA severity than either treatment alone.